A study of children with learning disabilities and sensorimotor problems or let's not throw the baby out with the bathwater. - Schaffer R; Law M; Polatajko H; Miller J (Physical & Occupational Therapy in Pediatrics, 1989)
The 1986 position statement by the Board of Trustees of the Council for Learning Disabilities called for a moratorium on the measurement and training of perceptual and perceptual-motor function as a part of services for children with learning disabilities (LD). Estimates in the literature, however, indicate that approximately 13% of children with LD exhibit motor deficits. Such children with motor or perceptual-motor problems are often referred to occupational therapy and found to have sensory integrative (SI) dysfunction; subsequently, they are treated with techniques aimed at remediating perceptual or sensorimotor dysfunction. Because the results of research concerned with the efficacy of sensorimotor therapy are inconclusive and incomplete at this time, the position statement may be premature. Occupational therapists, however, must be aware of the statement and respond appropriately. In order to respond, they must have a better understanding of the nature of this subgroup of children with LD who have motor problems. The purpose of this study was to assist in the definition of this population. Eighty children with LD between 5 years and 8 years 11 months were examined. They had been referred for occupational therapy at six centres in Southern Ontario. Results indicated that these children were similar to other children with LD in terms of gender and IQ distribution, developmental history, and academic achievement. The study population, however, tended to have less generalized emotional/behavioral disorder than the general population with LD. As expected, these children also had major deficits in gross and fine motor performance. A focus of the paper is on the importance of sensorimotor deficit for learning and self-concept in the child. Implications for both the position statement and practice and research in occupational therapy are discussed.